2010
DOI: 10.1002/pssa.201026270
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of breakdown characteristics in AlGaN/GaN/AlxGa1−xN HEMT based on a grading AlxGa1−xN buffer layer

Abstract: To improve the breakdown characteristics of an AlGaN/GaN based high electron mobility transistor (HEMT) for high voltage applications, AlGaN/GaN/AlxGa1−xN double heterostructure (DH‐HEMTs) were designed and fabricated by replacing the semi‐insulating GaN buffer with content graded AlxGa1−xN (x = x1 → x2, x1 > x2), in turn linearly lowering the Al content x from x1 = 90% to x2 = 5% toward the front side GaN channel on a high temperature AlN buffer layer. The use of a highly resistive AlxGa1−xN epilayer suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 13 publications
(19 reference statements)
2
11
0
Order By: Relevance
“…The off‐state leakage current at 200 V (the maximum limit of our measurement system) of sample A and sample B are 0.61 mA and 0.41 mA, respectively. Both structures demonstrate breakdown voltages much higher than that of the reference devices . While the HEMTs with only the AlN buffer, (structure A) show a degradation of the maximum drain current and the transconductance, the HEMTs devices based on structure B, with the HT AlN IL and the HLHT AlN, show that the maximum drain current and the transconductance are comparable with the published literature .…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The off‐state leakage current at 200 V (the maximum limit of our measurement system) of sample A and sample B are 0.61 mA and 0.41 mA, respectively. Both structures demonstrate breakdown voltages much higher than that of the reference devices . While the HEMTs with only the AlN buffer, (structure A) show a degradation of the maximum drain current and the transconductance, the HEMTs devices based on structure B, with the HT AlN IL and the HLHT AlN, show that the maximum drain current and the transconductance are comparable with the published literature .…”
Section: Resultssupporting
confidence: 68%
“…Several solutions have been developed to reduce the buffer leakage, such as doping intentional/unintentional acceptors into the GaN buffer, or considering a p‐GaN as a back‐barrier, however it is very likely that there are several kinds of traps or defects that may adversely affect the reliability of the device in AlGaN/GaN HEMT . Ozbay and co‐workers have reported that highly resistive GaN layers can be achieved by the growth of a thick HT AlN (0.5 − 1.0 µm) buffer layer on sapphire substrates, however the breakdown voltage of their device was only 60 V. The low breakdown voltage of AlGaN/GaN HEMTs with HT AlN may be due to residual donors in GaN (such as O and Si) incorporated during high‐temperature growth. Because it is necessary to compensate for the residual n‐type conductive GaN buffer to further improve the breakdown voltage of AlGaN/GaN HEMTs on both sapphire substrates and SiC substrates, AlGaN is also widely used to replace GaN buffers to enhance the breakdown .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At high drain-source bias electrons are injected under the gate depletion region creating a current path in the buffer. The punch-through effect can be suppressed by using a double heterojunction structure (DHFET), where the electron channel is confined between the upper barrier and a low Al-content Al x Ga 1-x N buffer layer [1,2].…”
mentioning
confidence: 99%
“…The conduction band off-set (DE c ) between Al 0.05 Ga 0.95 N and the nid GaN channel of about 0.06 eV can prevent electrons from penetrating into the GaN:C buffer. 18 The conduction band of the AlGaN back barrier doped with Si (structure C) is shown to be depleted. However, the conduction band offset is still present.…”
mentioning
confidence: 99%